2008
DOI: 10.1124/dmd.108.022004
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic Reduction and Glutathione Conjugation of Benzoquinone Ansamycin Heat Shock Protein 90 Inhibitors: Relevance for Toxicity and Mechanism of Action

Abstract: ABSTRACT:Two-electron reduction of benzoquinone ansamycin (BA) heat shock protein (Hsp) 90 inhibitors by NAD(P)H:quinone oxidoreductase 1 (NQO1) to hydroquinone ansamycins (BAH 2 s) leads to greater Hsp90 inhibitory activity. BAs can also be metabolized by one-electron reductases and can interact with glutathione, reactions that have been associated with toxicity. Using a series of BAs, we investigated the stability of the BAH 2 s generated by NQO1, the ability of BAs to be metabolized by one-electron reductas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
59
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(65 citation statements)
references
References 33 publications
4
59
1
Order By: Relevance
“…Such compounds do not degrade NQO1 but still show HSP90 inhibition (39), and they might be more efficacious with reduced toxicity. It is possible that the benzoquinone moiety binding to mitochondria may explain the liver toxicity of 17AAG observed clinically (5,40,41). Others have shown that tumor cells organize an intramitochondrial HSP90 and TRAP-1 chaperone network and regulate mitochondrial permeability transition (8).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such compounds do not degrade NQO1 but still show HSP90 inhibition (39), and they might be more efficacious with reduced toxicity. It is possible that the benzoquinone moiety binding to mitochondria may explain the liver toxicity of 17AAG observed clinically (5,40,41). Others have shown that tumor cells organize an intramitochondrial HSP90 and TRAP-1 chaperone network and regulate mitochondrial permeability transition (8).…”
Section: Discussionmentioning
confidence: 99%
“…17AAG and all GA derivatives have quinone moieties that are metabolized by NAD(P)H: quinone oxidoreductase1 (NQO1) (4,5). Kelland et al (6) first reported the relationship between levels of NQO1 and the sensitivity to 17AAG.…”
mentioning
confidence: 99%
“…Impaired liver function is commonly observed under treatment with BAderived HSP90-i (10). However, the molecular scaffold of IPI-493, which is related to 17-AAG, shows improved pharmacologic properties (35). According to in vitro data, IPI-493 presents higher potency in comparison with other HSP90-i (17).…”
Section: Discussionmentioning
confidence: 99%
“…Considering the similar effects of the two different approaches (interfering RNA and drug treatment in different cells), we are confident that the apparent common antiviral effect is the result of the specific inhibition of cellular HSP90 activity. Indeed, the two chemically distinct HSP90 inhibitors we used decrease the chance of observing a biological effect related to any "off-target" activity, as reported in the case of 17-DMAG (49,50). Furthermore, the mechanism of action of both drugs is well characterized, as shown by their perfect docking into the ATPase site of HSP90 (44,51).…”
Section: Hsp90 Activity Is Required For Mev Growth At a Postentry Stepmentioning
confidence: 97%